Fear of progression in patients with acute myocardial infarction: a cross-sectional study - Xinghui Wang; Nan Jiang; Shuoxin Chen; Subinuer Tuerdi; Jiayu Yang; Rong Yan; Li He; Jiajia Wang; Yuewei Li (BMC, 2024)
Abstract Background Acute myocardial infarction (AMI) is the most serious manifestation of coronary artery disease. At present, existing treatments cannot change the risk factors for the occurrence of the disease, so patients are prone to fear of progression or recurrence, and studies have shown that excessive fear will cause patients to over-examine, mental abnormalities, suicide and other behaviors, increase unnecessary medical care costs and the social medical burden. Thus to investigate the current situation of progression fear in patients with Acute Myocardial Infarction (AMI) admitted to hospital in stable stage and analyze its influencing factors. Methods This is a cross-sectional study. In this study, 160 AMI patients admitted to the Department of Cardiology of a 3 A hospital in Changchun from November 2022 to April 2023 were selected as the research sample by a convenient sampling method. Patients completed the general information questionnaire, the Fear of Progression Questionnaire-Short Form (FoP-Q-SF), the Brief Illness Perception Questionnaire (BIPQ), the Medical Coping Modes Questionnaire (MCSQ), the Social Support Rating Scale (SSRS), and the Positive Psychological Questionnaire (PPQ) at the time of stable condition. Using SPSS 25.0 software for data analysis, statistical methods mainly include descriptive statistics, analysis of variance, Pearson correlation analysis and multiple linear regression analysis. Results A total of 160 subjects were included, among which the score of simplified fear of progression scale was (33.43 ± 7.09), and the incidence of disorder of fear of progression was 50.60%. The influencing factors included gender (Beta = 0.118, P<0.05), disease perception (Beta = 0.445, P<0.001), psychological capital (Beta=-0.252, P<0.05) and resignation (Beta = 0.167, P < 0.05). Conclusion The overall level of fear of progression in patients with AMI at the stable stage of hospitalization is above the medium level. Nursing staff should focus on AIM patients suffering from multiple diseases and lacking awareness of their own diseases, and provide personalized health guidance and psychological nursing targeted to improve patients' rehabilitation, quality of life and FoP level.